THE SIGNIFICANCE OF MICROGRANITOID ENCLAVE SHAPES AND ORIENTATIONS - Paterson S.R.; Pignotta G.S.; Vernon R.H. (My University, 2004)
Enclaves are often incorrectly used to measure magmatic strains in plutons. We emphasize that microgranitoid enclaves are not like other ellipsoidal markers used to determine strain for the following reasons. (1) Adjacent enclaves may form at different times and different places and initially have non-spherical shapes with axial ratios up to 2.7. (2) The final shapes and orientations of enclaves are a complex function of (a) initial shape and temperature of enclaves, (b) subtle changes in composition, melt percents, volatiles, grain sizes, and thus temporally variable viscosity contrasts between the enclave and magma, (c) a competition between strain and interfacial energies, and (d) deformation path, which may include internal strain and rigid rotations caused by magma flow during ascent, convection, expansion, chamber boundary processes, and tectonism. (3) Enclaves spend much of their time in magma as relatively rigid objects, and thus rigidly rotate and potentially break apart, rather than strain at matrix strain rates. (4) In some instances, enclaves do not record or track finite strain. Because of the above, final enclave populations are heterogeneous, and the use of single enclaves or enclave populations as strain markers violates many assumptions needed to complete strain analyses. On the other hand, a comparison of the preserved characteristics of igneous layering, mineral fabrics, and carefully evaluated enclave fabrics, including internal mineral alignment in enclaves, may provide qualitative data on the changing magnitude and kinematics of magmatic strains.
Keywords: Expanding plutons; Rf/f analyses; Granites; Igneous enclaves; Magmatic foliations; Microgranitoid enclaves; Strain analyses